Application of Process Simulation Software METSIM in Metallurgy - Zhao Qiuyue; Zhang Tingan; Lv Guozhi; Zhu Xiaofeng (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Now the using of process simulation software is more and more widely in many fields especially in chemistry and metallurgy plant designing. The process simulation software provides great convenience for experts and engineers, they can analysis the new process and calculate the heating/material balance by process simulation software, and calculate complex process that the traditional tool EXCEL can not do. The paper introduced the current major process simulation software, includes mainly introducing the application of METSIM and SYSCAD software in metallurgical process, and summary the computational process of them by a few examples, at the same time the application status of the process simulation software was pointed out. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1660